Azerbaijan’s Quest for Strategic Autonomy - Tabib Huseynov (Ukrainian Policymaker)
This article explores Azerbaijan’s evolving more assertive foreign policy doctrine, which began to take shape following its victory over Armenia in the 2020 Second Karabakh War and was further solidified after its 2023 blitzkrieg operation, which dismantled institutionalized separatism within its territory. Conceptualized through the framework of strategic autonomy, this new doctrine is firmly anchored in realist and neorealist schools of thought, emphasizing pragmatic, interest-driven relationships with major regional and global powers while avoiding geopolitical entanglements. The paper argues that Azerbaijan’s quest for strategic autonomy is both a response to external pressures and a means to assert agency within the broader Eurasian security landscape. It also describes Azerbaijan as a «geopolitical connector», capable of punching above its weight in contributing to international security, owing to its strategic location and diplomatic outreach across opposing blocs. The paper enriches scholarly discussions on strategic autonomy with a practical case study, offering a novel analytical framework to understand Azerbaijan’s foreign policy and its potential impact on regional and global geopolitics.